2014
DOI: 10.1002/bio.2672
|View full text |Cite
|
Sign up to set email alerts
|

Study of luminescence and effect of Dy3+ on NaMgSO4Cl:Ce chlorosulphate phosphor

Abstract: Chlorosulphate NaMgSO4 Cl phosphor doped with Ce(3+) and co-doped by Dy(3+) prepared by the wet chemical method was studied for its photoluminescence and thermoluminescence (TL) characteristics. The emission spectrum of Ce(3+) shows dominant peaks at 346 nm (excitation 270 nm) due to 5d → 4f transition. Efficient energy transfer occurs from Ce(3+) → Dy(3+) ions. Dy(3+) emission at 485 nm and 576 nm is due to (4)  F9/2 → (6) H15/2 and (4)  F9/2 → (6) H13/2 transitions of Dy(3+) ion respectively. The TL glow cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Modern technology demands new UV sources especially for scintillation [1], for read heads to reduce data storage space, and for bio-imaging applications [2]. ZnS is a semiconductor material with large exciton binding energy of about 40 meV at room temperature [3].…”
Section: Introductionmentioning
confidence: 99%
“…Modern technology demands new UV sources especially for scintillation [1], for read heads to reduce data storage space, and for bio-imaging applications [2]. ZnS is a semiconductor material with large exciton binding energy of about 40 meV at room temperature [3].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation techniques and properties of various TL materials have been studied to date and it is observed that mixed sulfate is an excellent class of TL phosphor, especially when doped with suitable activators . Figure shows the TL glow curves of Na 15 (SO 4 ) 5 F 4 Cl:Ce 3+ phosphors for different concentrations of Ce 3+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its high energetic position, this emission could only be observed in lattices with optical absorption at high energy. The Gd 3+ ion, which has strong UV absorption, can act as sensitizer if the Ce 3+ emission in the given host matches the Ce 3+ absorption . Quite often energy transfer from the 6 P manifold of Gd 3+ to other RE ions or host lattice group occurs.…”
Section: Resultsmentioning
confidence: 99%